Development of an Ointment to Medicate Medicine for Dosage Caused by Mucus in Babies with the Active Compound Sotong (Sepia sp.) and Essential Oils Cymbopogon citratus - Hakim, Aliefman; Burhanuddin, Burhanuddin; Siahaan, Jeckson; Irawan, Jono; Fitri, Zelisa Nudia (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Sumbawa society is rich in culture, especially in traditional medicine. People use materials from the surrounding environment, including plants and animals, as active ingredients for medicine. Newborn babies and toddlers are susceptible to blockage of the respiratory tract with mucus. In babies, it is usually caused by an imperfect suction process, while in toddlers, it is caused by bacteria or viruses. The Samawa people use a mixture of cuttlefish (Sepia sp.) and eucalyptus oil as a medicine that effectively removes mucus from the body. The active ingredient in cuttlefish has an unpleasant odour and cannot be stored for long. When they need cuttlefish, people must look for them in markets or traders on the coast. Of course, this takes time to use. The ointment production innovation has many advantages, including practicality, no fishy smell, ease of obtaining, and ease of storage for the long term. Using the natural active ingredient lemongrass, essential oil adds aromatherapy and provides warmth to the chests of babies and toddlers. Natural active and gel-based ingredients are safe to use without side effects. The ointment was tested for active ingredient content using GCMS and organoleptic tests for gel stability, spreadability (homogeneity), pH, and skin irritation. Based on the description above, it can be concluded that the ointment product is made from an anti-skin irritation gel base, pH 7, and gel spreadability of 5.5 cm. The active substance comes from cuttlefish Sepia sp. by inhibiting the COX-2 enzyme and reducing the production of prostaglandin E2 (PGE2), an essential inflammatory mediator in the pathogenesis of asthma and bronchitis. The simple production process means that the price of the ointment is within people's purchasing power.